KEPEMIMPINAN TRANSFORMASI DALAM MANAJEMEN KEARSIPAN - Dhiya Rahma; Muhammad Syukur Badiul Alam; Siti Chilma Ladaina; Winda Husna Aghitsna; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of transformational leadership in archival management and its impact on the effectiveness of records management within organizations. Transformational leadership is considered an approach that encourages change, innovation, and improvement in human resource performance, including in the archival field. This research employs a qualitative approach with data collection techniques including interviews, observations, and documentation. The results indicate that leaders who apply a transformational style are able to increase awareness of the importance of archives, encourage digitalization, and foster a more adaptive and collaborative work culture. Furthermore, this leadership style plays a significant role in enhancing the competence of archival staff through continuous guidance and motivation. Therefore, transformational leadership has a strategic role in improving the quality of archival management. Keywords: transformational leadership, archival management, records effectiveness, organizational innovation